Newcomb’s Problem and the American Question - Norkus, Zenonas (Problemos, 2003)
The article introduces Lithuanian rcader into the work related to the Neweomb’s problem in the decisíon theory made famous by R. Nozick. The problem is decribed as that of the conflict between the dominancee principle and the maximization of the conditional expected utility (CEU) principle. This conflict arises in the situations where an actor has to choose between the action bespeaking good news that a desirable state of world obtains upon which the chosen action has no causal influence, and the action bespeaking bad news but causally efficient to produce a small benefit. The decisíon theorists are almost unanimous in the opi- nion that the contradiction between both principles of the rational choice must be solved at the expense of the CEU maximization principle. However, some of them (evidentialists - E. Eells, R. Jeffrey) maintain that the classical decisíon theory if properly applied reeommends the correct - „bad news, small benefit“ - choice, whereas others (causalists - J. Joyee, D. Lewis, B. Skyrms at al.) plead for its replacing by the causal decision theory. After introducing the reader into the present problem situation in the decision theory, the author concentrates on the version of the Newcomb’s problem involving the Predictor and discusses the neglected question what is the best explanation for the Predictor’s stunning suecess? To explain this success, the assumption is sufficient that the Predictor is able to discover whether an actor is bright ( = is prone to choose in the Neweomb-like situations according to dominance principle) or is stupid or only boundedly rational (including the case where he is prone to reason in the straightforward CEU-maximization way). So the actor’s rationality or its absence is the common cause of actor’s „bad news, small benefit“ choices and of Predictor’s predictions who is discriminating against the bright actors (including all causal decision theorists, of course) by providing for them no opportunity to avoid undesirable state. Therefore, the version of Neweomb’s problem involving the Predictor is about the situations where aetofs dispositional rationality is not a bonus but the plague causing him to tai] (the Prisonerls Dilemma situations are of the same kind). The American question argu- ment in favor of „good news“ choice draws its persuasive force from the implausibility of the instrumental rationality dooming its possessors to be permanent failures and of unreason vouching for constant success.